Erythropoietin: a novel therapy for hypoxic–ischaemic encephalopathy?. (April 2015) - Wu, Yvonne W; Gonzalez, Fernando F
Abstract : Perinatal hypoxic–ischaemic encephalopathy (HIE) occurs in 1 to 3 per 1000 term births. HIE is not preventable in most cases, and therapies are limited. Hypothermia improves outcomes and is the current standard of care. Yet, clinical trials suggest that 44–53% of infants who receive hypothermia will die or suffer moderate to severe neurological disability. In this article, we review the preclinical and clinical evidence for erythropoietin (EPO) as a potential novel neuroprotective agent for the treatment of HIE. EPO is a novel neuroprotective agent, with remarkable neuroprotective and neuroregenerative effects in animals. Rodent and primate models of neonatal brain injury support the safety and efficacy of multiple EPO doses for improving histological and functional outcomes after hypoxia‐ischaemia. Small clinical trials of EPO in neonates with HIE have also provided evidence supporting safety and preliminary efficacy in humans. There is currently insufficient evidence to support the use of high‐dose EPO in newborns with HIE. However, several on‐going trials will provide much needed data regarding the safety and efficacy of this potential new therapy when given in conjunction with hypothermia for HIE. Novel neuroprotective therapies are needed to further reduce the rate and severity of neurodevelopmental disabilities resulting from HIE. High‐dose EPO is a promising therapy that can be administered in conjunction with hypothermia. However, additional data are needed to determine the safety and efficacy of this adjuvant therapy for HIE.